2019
DOI: 10.1002/jmor.21065
|View full text |Cite
|
Sign up to set email alerts
|

Variation of organ position in snakes

Abstract: The complex and successful evolutionary history of snakes produced variation in the position and structure of internal organs. Gravity strongly influences hemodynamics, and the impact on structure and function of the cardiovascular system, including pulmonary circulation, is well established. Therefore, we hypothesized that interspecific variation in the position of the heart and vascular (faveolar) lung should exceed that of other internal organs that are less sensitive to gravity. We examined the position of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Perez et al (2019) examined the position of specific internal organs in 72 snakes across 13 species. The results corroborated the influence of gravity on the morphology of the cardiopulmonary system, and indicated that the gravity-sensitive vascular lung varied the most among all organs [ 65 ].…”
Section: Gravity and Evolutionsupporting
confidence: 66%
See 2 more Smart Citations
“…Perez et al (2019) examined the position of specific internal organs in 72 snakes across 13 species. The results corroborated the influence of gravity on the morphology of the cardiopulmonary system, and indicated that the gravity-sensitive vascular lung varied the most among all organs [ 65 ].…”
Section: Gravity and Evolutionsupporting
confidence: 66%
“…Thus, he suggested that sea snakes are mainly influenced by gravity, considering that they faint with increased gravity, whilst tree snakes are gravity-tolerant. Perez et al (2019) examined the position of specific internal organs in 72 snakes across 13 species. The results corroborated the influence of gravity on the morphology of the cardiopulmonary system, and indicated that the gravity-sensitive vascular lung varied the most among all organs [65].…”
Section: Gravity and Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body size and shape of reptiles and amphibians often reflect adaptation to microhabitats in which they occur (Citadini et al, 2018; Lillywhite, 1996; Lillywhite & Henderson, 1993; Losos, 1990; Martins et al, 2001; Perez et al, 2019). Our results on the five sympatric Chironiu s species reveal a marked variation in body morphology and a strong relationship with substrate use and diet.…”
Section: Discussionmentioning
confidence: 99%
“…Other measurements of shape remain largely unexplored. Body shape also influences the distribution of organs involved in the pumping and distribution of blood (e.g., heart and vascular lung) 29 , and interestingly, blood distribution is an important factor in regulating the temperature of ectothermic animals 30 . Additionally, the shape is associated with the rate at which processes such as the diffusion of matter and thermal conduction occurs 17 .…”
mentioning
confidence: 99%